Sebuah Penerapan la ibrata littawahumi pada transaksi utang piutang - Muhammad Arman Fariz (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research contains an explanation of the branch of the creed "la ibrata littawahumi," which is closely related to the main principle "al-yaqin la yuzalu bil-syak." The aim of this study is to understand the relationship between these two principles.This research contains an explanation of the branch of the creed "la ibrata littawahumi," which is closely related to the main principle "al-yaqin la yuzalu bil-syak." The aim of this study is to understand the relationship between these two principles.